The IMF and the World Bank : a case for separating the conjoined twins - Rieffel, Lex (The Brookings Institution WashingtonUS, 2008)
Suggests that putting the IMF and World Bank on course for the future will require two basic changes viz. lowering the profile of the United States in each institution and making them more separate from each other.